ASSESSMENT OF THE COMMUNICATIVE CAPACITY OF LOCAL SELF-GOVERNMENT AUTHORITIES IN CRISIS CONDITIONS (Coordinates of Public Administration, 2025)
The article examines the theoretical and methodological foundations for assessing the communicative capacity of local self-government bodies under various types of crises, including military threats, information attacks, and emergency situations. It substantiates the importance of communication activities for ensuring the resilience of territorial communities, maintaining operational governance, and fostering public trust in local authorities. The study emphasizes that in contemporary conditions, communication becomes a strategic instrument, as the effectiveness, accuracy, accessibility, and timeliness of information dissemination directly influence communities’ ability to respond to uncertainty and mitigate the consequences of crises.The article analyses current scholarly approaches to defining the essence of crisis communication and outlines the specific features of its implementation in Ukrainian territorial communities after 2022. It highlights the uneven development of communication practices and the absence of a unified national methodology for assessing communicative capacity, which complicates comparative evaluation and the formation of targeted managerial decisions. A four-dimensional model for assessing communicative capacity is proposed, comprising normative-organizational, technological-operational, content-related, and socio-psychological blocks of indicators. The study elaborates on the meaning behind each block and characterizes the indicators that enable a comprehensive assessment of a community’s readiness for crisis communication.Furthermore, the article substantiates the use of an integral communicative capacity index as a tool for strategic governance, allowing stakeholders to track the dynamics of communication development, identify weaknesses, and determine priority areas for strengthening institutional potential. The possibilities of applying such assessment in public administration practice are outlined, particularly for local self-government bodies, state administrations, international technical assistance programs, and civil protection structures. The study emphasizes that the introduction of a standardized assessment methodology will enhance community resilience, improve transparency in local governance, and support the formation of an effective system of crisis communication.